A Comprehensive Analysis of Building Construction Projects’ Delay Using the Analytic Network Process - Asdi, Ridzky Zul; Utomo, Dutho Suh (Cita konsultindo, 2025)
Delays in construction projects have emerged as a significant challenge due to their profound impact on costs, quality, and project timelines, all of which ultimately affect the overall success and completion of the project. The primary objective of this study is to identify the factors contributing to delays in building construction projects and to quantitatively assess the extent to which each of these factors influences project delays. To achieve this, a quantitative impact analysis of each identified factor is conducted using the Analytic Network Process (ANP). Five key factors have been identified as major contributors to project delays: design or specification changes, material procurement delays, adverse weather conditions, regulatory and permitting issues, and unforeseen risks. Among these, material procurement delays emerged as the most significant contributor, accounting for 36.13% of the total delay impact. This is followed by design or specification changes, unforeseen risks, regulatory and permitting issues, and adverse weather conditions. Further research is required to develop effective preventive measures to mitigate these delays and enhance project management practices.